The oniric trip - Gomes, Álvaro Cardoso (Revista de Letras, 2015)
This article intends to show that poetry book Memória Grega e Outros Poemas Viajantes, by Péricles Prade, belongs to the ancient tradition of “travel books”, written, over time, by travelers like Pliny, Marco Polo, Fernão Mendes Pinto, Daniel Defoe, Swift, Garrett, Humboldt. In this type of book, generally one “eudeambulante” in perpetual motion, using observation, memory and imagination, develops a poetic script, inspired by different spaces, beings, objects that have impressed him and deserved poetic representations.